The Impact of Human Papilloma Virus Among Sexually Active Youths and Suggested Primary Preventive Strategies - Ebomoyi, Josephine Itota; Ebomoyi, William (Advances in Social Sciences Research Journal, 2019)
The objective of the research was to assess the awareness of college age students about HPV variants and to determine suggested primary preventive strategies by respondents. The study also explored health education approach to create more awareness about the disease. HPV is one of the common sexually transmitted infections worldwide. It is linked to several cancers such as cancer of the cervix, vagina, vulva, head and neck, anal, and penile carcinomas. The instrument utilized was a questionnaire administered to students with the cooperation of other instructors. Of the 265 students surveyed, 180 were females and 73 were males. Many participants (84.5%) had heard about HPV. However, not all were aware of the numerous variants of the virus and the link to cancer. Regarding the knowledge about different variants of HPV, 33% of the subjects were not aware. Those respondents who thought the variants were more than 10 were 54%. Only 10% of the participants thought there were 11-20 variants. Majority of the subjects (61.8%) chose abstinence as a primary preventive strategy while 31.3% chose condom. The implications of our investigation were discussed and recommendation for health and wellness information is emphasized.